Is the good book good enough? : evangelical perspectives on public policy - Ryden, David K. (Lexington Books, 2011)
"The political emergence of evangelical Christians has been a signal development in America in the past quarter century. And while their voting tendencies have been closely scrutinized, their participation in the policy debates of the day has not. They continue to be caricatured as anti-intellectual Bible thumpers whose views are devoid of reason, logic, or empirical evidence. They're seen as lemmings, following the cues of Dobson and Robertson and marching in lock step with the Republican party on the 'culture wars' issues of abortion, gay rights, and guns. Is The Good Book Good Enough? remedies the neglect of this highly influential group, which makes up as much as a third of the American public. It offers a carefully nuanced and comprehensive portrait of evangelical attitudes on a wide range of policies and their theological underpinnings. Each essay applies an evangelical lens to a contemporary issue - environmentalism, immigration, family and same-sex marriage, race relations, global human rights, foreign policy and national security, social welfare and poverty, and economic policy. The result thoroughly enriches our understanding of evangelicalism as a prism through which many view a wide range of policy debates"--Publisher description